Perubahan pH, Fe-larut, dan P-tersedia di Tanah Sulfat Masam Aktual (Sulfaquept) yang Diberi Pupuk Kandang Sapi dan Genangan Air - Noor Soleha; Bambang Joko Priatmadi; Zuraida Titin Mariana (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Organic matter application and water management were frequently applied to prevent the oxidation of pyrite in acid sulfate soils. The purpose of this study was to determine the effect of cow manure application with varying height of inundation on soil pH, soluble-Fe, and available P of acid sulfate soils. This study employed factorial treatments and in a completely randomized design. The first factor was the dosage of cow manure: 0, 10, and 20 t ha-1, while the second factor was various water depths: 5, 10, and 15 cm. Results of study showed that the interaction of cow manure and water depth did not affect soil pH, but single factor of the treatments (cow manure and water depth) significantly affected soil pH. The interaction of cow manure and water depths did not significantly decrease the solubel-Fe in the fourth week. The interaction of cow manure and water depths significantly increased P-availability in the fourth week. Results of this study demonstrated that cow manure application and water depth improved soil pH and P-availability of acid sulfate soils.